Flowering and fruit set under Malaysian climate of Jatropha curcas L. - Noor Alam, Noor Camellia; Abdullah, Thohirah Lee; Abdullah, Nur Ashikin Psyquay (Science Publications, 2011)
Problem statement: In recent years Jatropha curcas has drawn the worlds attention as it has the potential to replace fossil fuel as biodiesel. However, the biggest setback in Jatropha cultivation in Malaysia is the low percentage of fruit set and the high ratio of male to female flowers. In order to further understand the flowering and fruit characteristics of Jatropha, floral and fruit development timeline is needed in order to develop solutions for the problems in low fruit set. Approach: This study described the flowering behaviour of Jatropha curcas cultivated under Malaysia and tropical climate. Investigation was carried out by observing the floral morphology, flowering sequence of pistillates, floral anthesis time, flower daily anthesis, flowering and fruiting plant behaviour, flower sex and fruit set ratio. Floral reproductive organs were examined using Scanning Electron Microscope (SEM). Results: Jatropha is monoecious and produces individual flowers in a dichasial cyme. Each Jatropha inflorescence has at least six compound cymes. Male flower anthesis started the earliest at 12.00 am and again at 6.10-6.46 am. Female flower anthesis commenced at 6.35-8.25 am. Male flowers opened for a period of 8-11 days, while female flowers opened for only 3-4 days. The reading of the male to female flower ratio was taken twice, 22: 1 in December 2008 and 27: 1 in April 2009. The flower to fruit ratios were 6: 5 (January 2009) and 2: 1 (May 2009). Numerically, 0-10 female flowers and 25-215 male flowers are produced in the same inflorescence. In this study, the terminal stem of Jatropha bears fruits profusely in January, May and August 2009. Development of the floral meristem consists of three stages that include a vegetative stage, transition from vegetative to floral stage and the development of flower parts. The meristem was in the transition stage at day 6. All Sepals and a petal were developed at day 18 but there was no presence of reproductive organs developing at this stage. Flower and fruit development takes approximately 3 months to complete the cycle from the initiated floral bud stage until fruit maturity. Conclusion: Continuous flowering and the incidents where flowering terminated in the middle of the flowering period were factors believed to cause the wide range of fruit ripening times recorded. The problem of small number of fruits produced in Jatropha curcas is mainly caused by the small number of pistillate flowers present in each inflorescence that range from 0 to 10 flowers in the same inflorescence. Jatropha could have two to four cyclical fruiting peaks in Malaysia.